Infectious complications in patients treated with immune checkpoint inhibitors. (December 2020) - Karam, Jean-Denis; Noel, Nicolas; Voisin, Anne-Laure; Lanoy, Emilie; Michot, Jean-Marie; Lambotte, Olivier
Abstract: Objective: Immune checkpoint inhibitor (ICI) antibodies constitute a new generation of cancer treatments, associated with immune-related adverse events (irAEs). A previous retrospective study of patients with metastatic melanoma (treated mostly with anti-CTLA4 antibodies) reported a serious infection rate of 7.3%. The main risk factors were corticoids and infliximab use. We sought to describe infections and risk factors among patients receiving anti–PD-1/PD-L1 ICIs. Patients and methods: We reviewed 200 medical records sampled randomly from a French prospective registry, which collates patients treated with anti–PD-1/PD-L1 ICIs. We recorded demographic data, the occurrence of irAEs, immunosuppressant use, and the outcome. Results: Thirty-six patients (18%) experienced an infection by a median (interquartile range) of 47 (19.2–132) days after initiation of the ICI. Twenty-one patients (58.3%) had a lung infection, seven (19.4%) had a skin infection, seven (19.4%) had a urinary tract infection, and all of them received antibiotics. The infection was generally mild, and the patients were treated as outpatient. There were no infection-related deaths and no opportunistic infection. Sixty percent of the patients were being treated for metastatic melanoma and 35.5% for non–small cell lung cancer, and 106 irAEs (mostly grade II) were reported. Forty-seven patients received steroids for cancer symptoms or irAEs, and five received immunosuppressants during the immunotherapy. We did not observe any association between corticosteroid or immunosuppressant use and the occurrence of an infection. Conclusion: The infection rate in patients treated with an anti–PD-1/PD-L1 ICI was 18%, without any severe or opportunistic infection. The occurrence of an infection was not associated with corticosteroid or immunosuppressant use. Highlights: Infections were searched for in 200 records from patients treated with ICIs. The infection rate was 18%, without any severe or opportunistic infection. Twenty-one patients (58.3%) had a lung infection. The occurrence of an infection was not associated with immunosuppressant use.